زيت لبدة الكبرى وغرامة يوليوس قيصر: دراسة تحليلية حول هوية المدينة وكمية الغرامة (Journal of Academic Research, 2025)
This study addresses the annual fine of olive oil imposed by Julius Caesar on the city of Leptis following the Roman Civil War in 46 BC, the research focuses on two main issues: first, identifying the city subject to the fine—whether it was Leptis Magna or Leptis Minor; and second, conducting a quantitative analysis of the fine, which amounted to 3,000,000 Roman pounds.By applying both the historical-analytical method and the quantitative approach, the study concludes that Leptis Magna was the city concerned with this fine, based on a set of historical evidence and testimonies, Furthermore, the study demonstrates that the fine exceeded the capacity of a single city to meet, It required the support of its agricultural hinterland as well as the other cities of the Tripolitanian region, The findings also reveal that Caesar was well aware of the economic potential of Leptis Magna and its region, particularly in relation to olive oil production.